2018
DOI: 10.1155/2018/2758347
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Carbon-Based Coating as Potential Endovascular Material for Stent Surface

Abstract: Stainless steel 316L is a material commonly used in cardiovascular medicine. Despite the various methods applied in stent production, the rates of in-stent restenosis and thrombosis remain high. In this study graphene was used to coat the surface of 316L substrate for enhanced bio- and hemocompatibility of the substrate. The presence of graphene layers applied to the substrate was investigated using cutting-edge imaging technology: energy-filtered low-voltage FE-SEM approach, scanning electron microscopy (SEM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…Graphene is a single layer of sp 2 hybridized carbon atoms creating a hexagonal lattice, and possessing unique properties, i.e., high specific surface area (~2630 m 2 /g), high electron mobility [11,12], thermal conductivity of between 2-5 kW•(m•K) −1 , [13,14] and the highest known Young modulus (~1 TPa) [15,16]. Moreover, several studies showed that graphene exhibits some antibacterial properties [17][18][19][20]. Its antibacterial mechanism is due to both physical (direct contact of the sharp edge of graphene with bacterial membranes) and chemical (induction of the oxidative stress generated by charge transfer) perturbation.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene is a single layer of sp 2 hybridized carbon atoms creating a hexagonal lattice, and possessing unique properties, i.e., high specific surface area (~2630 m 2 /g), high electron mobility [11,12], thermal conductivity of between 2-5 kW•(m•K) −1 , [13,14] and the highest known Young modulus (~1 TPa) [15,16]. Moreover, several studies showed that graphene exhibits some antibacterial properties [17][18][19][20]. Its antibacterial mechanism is due to both physical (direct contact of the sharp edge of graphene with bacterial membranes) and chemical (induction of the oxidative stress generated by charge transfer) perturbation.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene coating to the stent surface significantly lowered the onset rates of in-stent restenosis and thrombosis. [179] The cardiovascular applications of nanocarbons essentially make them ideal materials for future generation medicine [180] and could be expanded to produce graphene or CNT based cardiovascular stent that can avoid adverse immune reactions of a metallic stent. With the introduction of 3D printing technology in regenerative tissue engineering, carbon nanomaterial-based bioresorbable stents seem to be a promising strategy that is yet to be explored.…”
Section: Nanocarbon Coatings For Cardiovascular Stentmentioning
confidence: 99%
“…Graphene coating to the stent surface significantly lowered the onset rates of in‐stent restenosis and thrombosis. [ 179 ]…”
Section: Application Of Nanocarbons To Cvdsmentioning
confidence: 99%
“…Graphene-coated stents have also been investigated for their anti-thrombogenic properties on stainless steel [ 30 , 31 , 32 ]. These coatings may show greater reduction in platelet adhesion compared to heparin-eluting stents, with some reducing adhesion by 80–90%, but these also show slightly elevated cytotoxicity compared to bare stents.…”
Section: Introductionmentioning
confidence: 99%